Human resource development for broadcasting in Asia - Hassan, Salleh (Martinus Nijhoff Publishers, 1986)
Broadcasting in Asia began with a whimper - with outdated equipment, borrowed personnel and limited demands from its audience. Over a span of some 40-50 years, it has grown in stature and, aided by the growth of electronic technology, has attained new and bigger dimensions.' Technological change and audience expansion have posed a challenge to broadcasting organizations. There is a demand for more diverse content and subject matter, especially in the countries now embarking upon development programs. The main problems of the broadcasting industry in the region are staff improvement to produce qualified personnel, and increasing the efficiency of current manpower. There is a strong consciousness that broadcasters are an important social resource and that their training is essential to the nation, not a dispensible luxury.